2003
DOI: 10.1111/1469-7610.00168
|View full text |Cite
|
Sign up to set email alerts
|

Strong genetic effects on cross‐situational antisocial behaviour among 5‐year‐old children according to mothers, teachers, examiner‐observers, and twins’ self‐reports

Abstract: This study and four others of very young twins show that genetic risks contribute strongly to population variation in antisocial behaviour that emerges in early childhood. In contrast, genetic risk is known to be relatively modest for adolescent antisocial behaviour, suggesting that the early-childhood form has a distinct etiology, particularly if it is pervasive across situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
157
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 92 publications
(94 reference statements)
13
157
0
1
Order By: Relevance
“…Parents may share with their children genetic characteristics which do not facilitate learning of emotional regulation and inhibition of overt aggression. Genetically informative studies such as twin, adoption, and molecular genetic studies are needed to test the contribution of genetic factors and the likely gene-environment interactions and geneenvironment correlations (e.g., Arseneault et al, 2003;Caspi et al, 2002;Dionne et al, 2003;Weaver et al, 2004) There are limitations to this study. First, the developmental patterns that we observed for PA do not necessarily generalize to other types of aggression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents may share with their children genetic characteristics which do not facilitate learning of emotional regulation and inhibition of overt aggression. Genetically informative studies such as twin, adoption, and molecular genetic studies are needed to test the contribution of genetic factors and the likely gene-environment interactions and geneenvironment correlations (e.g., Arseneault et al, 2003;Caspi et al, 2002;Dionne et al, 2003;Weaver et al, 2004) There are limitations to this study. First, the developmental patterns that we observed for PA do not necessarily generalize to other types of aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that such problematic levels of aggression in adolescence or adulthood can be identified in the preschool years (Keenan & Wakschlag, 2000) and can be traced to events occurring early in life (Arseneault et al, 2003;Caspi et al, 2002;Moffitt, Caspi, Rutter, & Silva, 2001;. However, no studies have mapped the development of PA between toddlerhood and adolescence or adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…1 Specific measures of antisocial behavior have been analyzed separately and have been reported to yield highly similar parameters in twin ACE models (Arseneault et al, 2003). ADHD-We examined this measure to ascertain whether IQ and antisocial behavior were associated among children who did not have the ADHD diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The scale reliability of the combined score was .94 at age 5 years and .95 at age 7 years as calculated according to the formula by Nunnally (1967). Given the young age of the sample and concerns about reliable measurement of antisocial behavior in young children, we created a composite variable of children's antisocial behavior in early childhood by totaling the two age-specific measures, which were correlated at .69, p < .001.1 Specific measures of antisocial behavior have been analyzed separately and have been reported to yield highly similar parameters in twin ACE models (Arseneault et al, 2003). ADHD-We examined this measure to ascertain whether IQ and antisocial behavior were associated among children who did not have the ADHD diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation